TYPES OF SYLLABLES IN THE WORKS OF “RED PROFESSOR” K. TYNYSTANOV AND ACADEMICIAN B. Ө. ORYZBAEVA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In the article, the work of academician Bubiyna Omurzakova Oruzbaeva “Speech Structure” contains 75 types of syllables for scientific analysis. The object of the study were root words in the “Kyrgyz-Russian” dictionary of K. K. Yudakhin. It includes 75 types, from monosyllabic words consisting of one vowel sound to 2-3-syllable words formed as a result of different placement of vowel-consonant sounds that form the shell of the word. According to this feature, 75 types of joints were identified. The mentioned 75 types are compared with the joint types developed by K. Tynystanov in the 2nd book of the dictionary of inventory number 161 of K. Tynystanov.
Keywords: root words, types of syllables, vocabulary, vowel sounds, consonant sounds, scientif- ic analysis, scientific concept